Computer prediction of acute toxicity of thioderivatives of 3,5-bis(5-mercapto-4-R-4H-1,2,4-triazol-3-yl)phenol - K. K. Isaicheva; A. H. Kaplaushenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2024)
This study presents the computational prediction of acute toxicity for new derivatives of 3,5-bis(5-mercapto-4-R-4H-1,2,4-triazol-3-yl)phenols and their alkylated analogues.